Vremia . Vremia . Time . Время - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Geneva's nuclear disarmament talk; National Teacher's Day. Series description: A television newscast, shown on Channel One Russia (since 1995), уфкдшук on the First Program of the Central Television of the USSR. The program has been on the air since January 1, 1968. From December 27, 1991 it became the main news program of the Russian Federation, starting January 1, 1992 it was aired as "Novosti"/News. The program name "Time" reappeared on December 16, 1994. The program has been produced till nowadays. It is produced by the Directorate of the information programs of Channel One (from 1996). Earlier it was produced by the Main Editorial Office of Information of the Central Television (1968—1991), by the Studio of information programs of the All-Union State TV and Radio Broadcasting Company (1991), and by Information Television Agency of the All-Russian State TV and Radio Broadcasting Company (1994-1995). It is broadcasted at 21:00 (from 1972) with the timing of 30 minutes, and until December 31, 1989 the program was repeated at 12:30. Женевские переговоры о ядерном разоружении; празднование Дня учителя. Описание серии: Информационная программа Первого канала России (с 1995), ранее Первой Программы Центрального телевидения (1968–1991). Впервые вышла в эфир 1 января 1968 года. С 27 декабря 1991 года программа стала одной из официальных информационных программ России и с 1 января 1992 года выходила в эфир как «Новости». Название «Время» было возвращено в заставку 16 декабря 1994 года. Программа выходит по настоящее время. Производится Дирекцией информационных программ Первого канала (с 1996), ранее производилась Главной редакцией информации Центрального телевидения (1968-1991), Студией информационных программ Всесоюзной государственной телерадиокомпании (1991), Информационным телевизионным агентством Всероссийской государственной телерадиокомпании (1994-1995). Выходит в эфир в 21:00 (c 1972 года) с хронометражем в 30 минут, до 31 декабря 1989 года выходил также повтор программы в 12:30.